Predicting genitourinary injuries in polytraumatized patients: development of the GUIPP scoring system - Bohe, Olivia Anna; Müller, Michael; Rittstieg, Philipp; Zehnder, Philipp; Lefering, Rolf; Biberthaler, Peter; Wenk, Maren; Hanschen, Marc (Journal of Clinical Medicine, 2023)
Background: The genitourinary system is not as commonly affected as many other organ systems in severely injured patients. Although a delayed and missed diagnosis of genitourinary injuries (GUIs) can severely compromise long-term outcomes, these injuries are frequently overlooked. Therefore, we present a scoring system designed to assist emergency physicians in diagnosing GUIs in severely injured patients. Methods: The data were obtained from the TraumaRegister DGU® from the years 2015-2021. All severely injured patients (ISS ≥ 16) ≥16 years of age and treated in Germany, Austria, or Switzerland were included in this study. We excluded patients who were transferred out early (48 h), and all patients with isolated traumatic brain injury. After the univariate analysis of the relevant predictive factors, we developed a scoring system using a binary logistic regression model. Results: A total of 70,467 patients were included in this study, of which 4760 (6.8%) sustained a GUI. Male patients (OR: 1.31, 95% CI [1.22, 1.41]) injured in motorcycle accidents (OR: 1.70, 95% CI [1.55, 1.87]), who were under 60 years of age (OR: 1.59, 95% CI [1.49, 1.71]) and had sustained injuries in multiple body regions (OR: 6.63, 95% CI [5.88, 7.47]), and suffered severe pelvic girdle injuries (OR: 2.58, 95% CI [2.29, 2.91]) had the highest odds of sustaining a GUI. With these predictive factors combined, a novel scoring system, the GUIPP score, was developed. It showed good validity, with an AUC of 0.722 (95% CI [0.71; 0.73]). Conclusion: Predicting GUI in severely injured patients remains a challenge for treating physicians, but is extremely important to prevent poor outcomes for affected patients. The GUIPP score can be utilized to initiate appropriate diagnostic steps early on in order to reduce the delayed and missed diagnosis of GUI, with scores ≥ 9 points making GUIs very likely.